TYPES OF SUBSTANTIVATION OF ADJECTIVES IN ENGLISH: MORPHOLOGICAL, SYNTACTIC, AND SEMANTIC PERSPECTIVES - Ro’ziyeva Aziza Abdivayetovna (Bright Mind Publishing, 2025)
This article explores the phenomenon of substantivation in English—specifically, the transformation of adjectives into nouns. Substantivized adjectives play an important role in English morphology and syntax, revealing how linguistic economy and abstraction operate in natural language. The paper investigates the structural mechanisms of substantivation, categorizes its types (complete and partial), and analyses its functions in modern English through authentic examples. Particular attention is paid to substantivation as a process reflecting social, cultural, and cognitive patterns.
Keywords: Substantivation, adjective, transformation, abstraction, structural mechanism, morphology and syntax.